The useful wild plants of Guinea: an analysis of socio-economically important species and implications for conservation - Molmou, Denise; Couch, Charlotte; Gosline, George; Ryan, Philippa; Burton, George P.; Haba, Pépé M.; Haba, Pierre K.; Konomou, Gbamon; Magassouba, Sékou; Diabate, Moussa; Keita, Soundiata; Doumbouya, Saïdou; et al. (Frontiers in Conservation Science, 2025)
IntroductionGuinea is one of the most biologically and culturally diverse countries in West Africa, home to over 3,500 native plant species and 20 ethnolinguistic groups. The country has a large rural population who mainly depend on these plants and their products for their livelihood. Traditional knowledge on plant uses is passed from generation to generation but is often not formally documented, which hinders sustainable development in Guinea.MethodsThis study aims to document the uses of the wild plant species in Guinea, through interviews with local communities in the four geographical regions of Guinea and a literature survey, to improve sustainable use and management of Guinea's plant resources. The conservation status of the useful native plant species and the potential threats to their survival are report. In addition, a comparison is presented between the four geographical regions of Guinea, in the context of their environmental and cultural characteristics.ResultsIn Guinea, at least 399 wild useful plant species are harvested, representing c. 10% of the total Guinean flora. Plants were mostly used for medicinal purposes (55% of species), materials (32%) and as a source of food (11%). Of these species, 28 have been assessed as globally threatened and six as near threatened, potentially impacting their long-term survival and use.DiscussionPlants contribute to the economic and social welfare of the people of Guinea. The data gathered in this study will be helpful to orientate future conservation efforts of wild useful plant species for future generations.